Association of abnormal oral habits with body mass index among 6-12-year-old school children in and around Melmaruvathur: A cross-sectional study - Lokesh Siva; R Krishnakumar; D K Sugumaran; G Mohan; S Syed Shaheed Ahamed; Anand Prabhu (Wolters Kluwer Medknow Publications, 2023)
Background: The habit of eating more of sugary drinks and foods with high in trans fats and excessive saturated fatty foods, when the person is in stress has an effect on the individual's weight. Objectives: To evaluate the body mass index (BMI) and determine its association with abnormal oral habits in 6-12-year-old school-going children. Materials and Methods: The 46 schools were selected based on simple random sampling technique and all children who were aged between 6 and 12 years were included in the study. Among 5525 children screened, 1665 (30.13%) had various types of abnormal oral habits. The BMI of these children was calculated. The obtained BMI values were compared using Chi-square test in IBM SPSS windows version 20 software, where P < 0.05 was considered statistically significant. Results: The association between bruxism, lip biting, nail biting, and pencil biting habits with their BMI was found to be statistically significant and other habits like thumb sucking, tongue thrusting, mouth breathing and masochistic habits with their BMI which was found to be statistically non-significant. Conclusion: The children with stress-related oral habits had high BMI and their associations were found to be statistically significant. Hence, identification of children with stress-related oral habits and sensitization of parents, teachers, and the caregiver is of great importance.